Readiness at what cost? Trauma, displacement and opportunism in the Florida Keys - Shtob, Daniel A. (Frontiers in Sustainable Cities, 2022)
As more jurisdictions adopt climate and disaster readiness plans in response to disaster risk, the merits of climate resiliency, adaptation, and recovery processes and initiatives should be assessed based upon their outcomes as opposed to their stated or implied intentions. This should involve assessment of the experiences of early adopters, to assist localities with plans currently under development. The key question explored is what factors combine to exacerbate displacement risk in the long tail of a disaster aftermath, especially at the understudied intersection of political economy and disaster trauma? To address this question, I use in-depth interviews with residents of the lower Florida Keys in the aftermath of 2017's devastating Hurricane Irma, identifying a complex of drivers through which risk of unequal residential displacement took shape. Specifically, post-Irma bureaucratic delays contributed to trauma promoted displacement in local working communities; in some cases, these processes resulted from preparedness initiatives themselves. In addition to the well-known displacement that occurs immediately after a storm, this suggests that displacement risk may develop over long timeframes as residents are emotionally and materially worn down by repeated frustrations. Identifying how disaster readiness initiatives contribute to these processes emphasizes the need for enhanced attention to the places and populations that they are intended to protect, as well as the generative power of their interactions with everyday bureaucracy and government function. Furthermore, this community's experiences invite future research to better understand how resilience, adaptation, and public safety initiatives interact with political economic context in ways that can result in sociospatial inequality, providing caution and suggesting avenues for reform.